Flood frequency analysis of Ramganga River Basin in Western Gangetic Plain, India - Mukherjee, Rameswar; Bilas, Ram (National Geographical Journal of India, 2022)
Flood frequency analysis (FFA) of major rivers of the Indo-Ganga-Brahmaputra plain is very essential for flood hazard assessment, mitigation as well as effective planning and management for the indigenous people. In the present study, FFA has been done on Ramganga river, located in Western Gangetic Plain region. The river in this region is notorious for flood hazards. Among the most popular FFA models, Gumbel, Weibull, and Log Pearson-III models have been applied for the present assessment. Goodness of fit tests also has been performed to find out the best fitting model. The study shows that Log Pearson-III model is recognized most suiTable than other models. To demonstrate the specific trend of seasonal discharge, Mann-Kendall statistical test has been used which shows a decreasing trend of monsoon discharge while an increase in summer and winter discharge